2010
DOI: 10.4034/1519.0501.2010.0103.0017
|View full text |Cite
|
Sign up to set email alerts
|

Oral and Dental Diseases among Children and Adolescents in Kano, Nigeria

Abstract: RESUMOObjeti vo: Revisar as característi cas das doenças orais e dentárias em crianças e adolescentes e analisar os serviços odontológicos realizados no Departamento de Cirurgiamaxilofacial do Hospital Escola Amino Kano, em Kano, Nigeria, em um período de dois anos. Método: Um estudo retrospecti vo foi realizado no período de julho de 2001 a junho de 2003 sendo analisadas várias doenças orais e dentárias. Results: Foram analisados 126 (58,1%) meninos e 91 (41,9%) meninas (proporção de 1,4:1) com idades entre 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…Furthermore, the mean plaque index score as compared to calculus score was also the major contributor to the overall mean oral hygiene index score recorded in gender, all age-groups and camp locations. Comparable observations were reported from previous studies where higher dental plaque index scores were noticed among children from low 3,9,13,20,21 socioeconomic status attributed to poor oral hygiene practices reported among children of 22 similar age category and environment. The mean calculus index score was also observed to increase with increasing age but vary with IDPs' camp locations in the study environment.…”
Section: Resultssupporting
confidence: 77%
“…Furthermore, the mean plaque index score as compared to calculus score was also the major contributor to the overall mean oral hygiene index score recorded in gender, all age-groups and camp locations. Comparable observations were reported from previous studies where higher dental plaque index scores were noticed among children from low 3,9,13,20,21 socioeconomic status attributed to poor oral hygiene practices reported among children of 22 similar age category and environment. The mean calculus index score was also observed to increase with increasing age but vary with IDPs' camp locations in the study environment.…”
Section: Resultssupporting
confidence: 77%
“…High incidence of plaque and calculus was also found among 66% of respondents in a survey done in Kwara State of Nigeria, with children aged 12 reporting higher incidence of plaque and gingivitis than the adult population while 13% incidence of dental caries was reported as the lowest oral condition in the state [7]. In a study done in Kano, a northern city in Nigeria, 49.8% of children and adults reported dental caries as the most common challenge [8], however, Osuh et al reported a higher prevalence of oral diseases among residents in slums compared with non-slum urban residents in Ibadan, a city in western Nigeria [9]. Oral health disease is on the increase in Nigeria and preventive strategy must be prepared after a comprehensive study on the spread of oral diseases is done.…”
Section: Introductionmentioning
confidence: 84%
“…Different parts of the mouth such as the teeth, gums or other tissues may be affected by dental disease. Apart from a toothache, which is a commonly experienced dental disease, others may manifest as inability to speak, smile or even chew with a varying degrees of severity (Sanu et al 2010 ). Dental disease affects people of all age groups and all races.…”
Section: Introductionmentioning
confidence: 99%
“…Most patients with dental problems in Africa and Asia present late with acute pain especially amongst the poor and deprived of these populations and with these sub-groups opting more for extractions which appear to be the norm. Although aesthetics is not a high priority for the poor patient in this setting and in selecting prosthetic replacement Kenndy’s class III denture is the choice for cost and aesthetic reasons (Ajayi et al 2012 ; Sanu et al 2010 ; Varenne et al 2005 ; Ehikhamenor et al 2010 ; Upadhyaya and Humagain 2009 ). Poor access and low utilisation of dental services due to anticipation of high charges, painful treatment, long waiting times among others is the hallmark of most government dental facilities within the African context (Bamise et al 2008 ; Åstrøm and Masalu 2001 ).…”
Section: Introductionmentioning
confidence: 99%